A rare case of unipennate third and fourth lumbricals arising from the flexor digitorum profundus tendon for the ring finger. Issue 15 (2013) - Ravindra, SS; Sirasanagandla, SR; Nayak, SB; Rao, KG Mohandas; Kumar, N
No abstract available